BOOKBINDING: A RELIC OR A VALUE? - KOLPAKOVAITĖ, AURIKA (Knygotyra, 2014)
Vilniaus universiteto Knygotyros ir dokumentotyros institutas Universiteto g. 3, Lt-01513 Vilnius, Lietuva El. paštas: aurika.kolpakovaite@gmail.com